Climate variability of southern high latitude regions : sea, ice, and atmosphere interactions - Khare, Neloy (CRC Press, 2022)
"This is the first book to provide a comprehensive overview of climate change-related investigations carried out by researchers in India through regarding initiatives in southern high latitude regions. It explains climate variability over the Southern Ocean and Antarctica; air, sea, ice, and atmosphere interactions and the impact of climate variability on sea, ice, and polar atmosphere. Using data gathered by two Indian research bases Maitri and Bharti, ideal sites to study and understand how Antarctic climate evolution has taken place in geological past and changed in the recent past, this book helps understand climatological perspectives and evaluate some of the most pressing issues in the south polar region"--
Antarctic ozone : trends and variability in a changing climate / V.K. Soni, Sanjay Bist, Jagvir Singh -- Stratospheric dynamics and its role in climate over the Antarctica / Karanam Kishore Kumar and N. Koushik -- Antarctic weather and climate patterns / Sunitha Devi S. and R.S. Maheskumar -- Antarctic aerosols and climate : measurements at a coastal Antarctic station / Vimlesh Pant, Devendraa Siingh, A.K. Kamra -- Transient variations in en route Southern Indian Ocean aerosols, Antarctic ozone climate and its relationship with HOx and NOx / S.M. Sonbawne, P.C.S. Devara, P.R. C. Rahul, K.K. Dani -- Physico-chemical properties of Antarctic aerosol particles / Vikas Goel, Sumit Kumar Mishra -- Impact of near-Earth space environmental condition to the Antarctic sub-auroral upper atmospheric region / Rupesh M. Das -- Intriguing relationship between Antarctic Sea ice, ENSO and Indian summer monsoon / Amita Prabhu, R.H. Kripalani and G. Pandithurai -- Quantifying the predictability of Southern Indian Ocean Sea ice concentration in a changing climate scenario / Suneet Dwivedi and Lokesh Kumar Pandey -- Antarctic decadal sea-ice variability / Alvarinho J. Luis -- Southern Hemispheric climate change, interhemispheric teleconnection, and the decreasing trends in the seasonal mean monsoon rainfall over the Indian Region in the last century (1871-2004) / Rajib Chattopadhyay and A.K. Sahai -- Spatio and temporal variability of physical parameters in the Prydz Bay for climate change / S.M. Pednekar.
Includes bibliographical references and index.
Keywords: Climatic changes -- Antarctica; Climatic changes -- Antarctic Ocean